Senior residents of Silesian cities and the social welfare system: challenges and dilemmas for local communities - Zwartka-Czekaj, Monika (Instytut Socjologii Uniwersytet Wrocławski, 2014)
The present study focuses on problems and challenges related to the needs of the elderly community, to be faced by local governments and other institutions that provide care and support to various social groups. These problems include economic factors (i.e. limited and often insufficient income), ailments, disabilities and chronic conditions affecting everyday existence, limited mobility and, in some cases, social alienation. In view of modern approaches to ageing which stress the importance of happiness and satisfaction derived from participation in the life of the local community, represented here by the theories of Helen Bee and George Maddox, it seems obvious that one of the most urgent goals facing social welfare and support systems is the development of programmes and schemes to help the elderly preserve their self-reliance and independence as much as possible given the present stage of development in medicine and social economy, while simultaneously enabling them to contribute to their social environment.
Keywords: senior citizens; pensioners; local communities; social policy